FAKTOR KEWASPADAAN STANDAR YANG BERKONTRIBUSI TERHADAP KEJADIAN HEALTHCARE-ASSOCIATED INFECTIONS (HAIs) PADA MASA PANDEMI COVID-19 DI RUANG RAWAT INAP RUMAH SAKIT "X" DEPOK - Farras Jihan Afifah (2021)
WHO estimates that 1.4 million people in the world will experience HAIs. In Indonesia, the incidence of HAIs reaches 15.74%. Compliance with the use of PPE in the "X" Depok Hospital 2020 on the 6th floor was 86.41% and 7th floor was 89.41%. Standard precautions are the scope of the IPC which aims to prevent HAIs. This study aims to measure the contribution of SP to the incidence of HAIs during the COVID-19 pandemic in the inpatient ward "X" Depok Hospital. This design is quantitative with a cross-sectional approach and equipped with qualitative through open question. The sampling technique was total sampling with a total of 43 nurses. Data were analyzed using Chi-Square and multiple logistic regression. The results showed that hand hygiene (p value = 0.006) cough etiquette (p value = 0.035), environmental cleaning (p value = 0.001) contributed to the incidence of HAIs. Meanwhile, the use of PPE, safe injection practices, waste management, linen handling, patient care equipment did not contribute to the incidence of HAIs. The results of multivariate analysis found that environmental cleaning contributed significantly to the incidence of HAIs (p value = 0.024). Nurses are expected to apply SP by increase awareness to prevent HAIs.